Games in Education: Exploring the Perception of School Teachers - Altaf, Faiza; Haider, Ali (THE PRIMARY TEACHER, 2019)
Games make learning experiences more realistic for learners. A child learns about teamwork, values, and the blending of a variety of skills through playing games. There has been a rapid shift away from more traditional games towards digital or online options. The inclusion of these digital games in education has both advantages and disadvantages. A good teacher in the twenty-first century needs to know how these games can be used in the classroom. As a result, it is of utmost importance to investigate how teachers make use of games for instructional purposes. The main objective of this study was to investigate how teachers use games in the classroom and how they see the role of games in the educational process. The sample for this study consisted of 48 teachers from government and private schools in Delhi, Uttar Pradesh, Uttarakhand, Rajasthan, and West Bengal. An online questionnaire was used to collect data from elementary, middle, and high school teachers. Additionally, the issues and difficulties associated with games in education were discussed. Despite the study’s limitations (such as its small sample size and other factors), its findings are interesting and may be useful to teachers, teacher educators, curriculum designers, and other stakeholders